2017
DOI: 10.25077/jip.1.1.11-21.2017
|View full text |Cite
|
Sign up to set email alerts
|

Budaya dan Perilaku Berjudi: Kasus Tajen Di Bali

Abstract: Abstrak. Judi telah lama dipahami sebagai aktivitas yang melibatkan penggunaan uang atau materi lainnya untuk suatu hasil yang bersifat tidak pasti. Judi juga diketahui dapat menimbulkan risiko pada kehidupan seseorang, meliputi masalah keuangan, masalah psikologis, hingga masalah hubungan interpersonal. Perilaku berjudi yang maladaptif juga telah dicantumkan dalam DSM-IV dengan nama judi patologis (312.31), serta dinyatakan ilegal di berbagai negara, termasuk Indonesia. Aktivitas berjudi dalam tradisi juga da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
(5 reference statements)
0
7
0
3
Order By: Relevance
“…Pola komunikasi pasangan antaretnis Sunda-Jawa di Kabupaten Ciamis (Duddy Zein, Wagiati, Nani Darmayanti) maupun dengan sesamanya, khususnya ketika mereka berkomunikasi dan berinteraksi dengan kalangan yang secara kultural berlainan. Kondisi inilah yang dinamakan dengan terminologi "perilaku budaya" (Aryanata, 2017;Gea, 2011;Sulistyawati & Santosa, 2019) Yusuf, 2020).…”
Section: Pendahuluanunclassified
“…Pola komunikasi pasangan antaretnis Sunda-Jawa di Kabupaten Ciamis (Duddy Zein, Wagiati, Nani Darmayanti) maupun dengan sesamanya, khususnya ketika mereka berkomunikasi dan berinteraksi dengan kalangan yang secara kultural berlainan. Kondisi inilah yang dinamakan dengan terminologi "perilaku budaya" (Aryanata, 2017;Gea, 2011;Sulistyawati & Santosa, 2019) Yusuf, 2020).…”
Section: Pendahuluanunclassified
“…Street cockfighting is called a branangan with a modest bet. Whereas cockfighting in the Tajen arena is carried out with clear norms, betting rules, the present of Tajen official (Saya), pakembar, and bebotoh [23]. That is the image of male Balinase.…”
Section: Bali As the Tourism Industry: Commodification Of Balimentioning
confidence: 99%
“…This study the researcher was found 12 compounding in jargons used in traditional cockfighting at Cempaga village. According to (Nordquist, 2018) Compounding is a because the installation of this spur fits perfectly with the target of the hit from the cock (Aryanata, 2017;Suastika, 2015). Cok balu is the jargon used by the traditional cock fighting at Cempaga village to find a bet, cok balu has the same meaning with cok.…”
Section: Teluinmentioning
confidence: 99%
“…Tajen in cultural activities is a legitimate form of tradition. Each movement must be accompanied by a red (blood sow) percussion ceremony derived from animals' blood, including cocks, based on the prevailing custom in Balinese ceremonies (Aryanata, 2017;Suastika, 2015). In essence, it is very evident that the relationship between cock and cockfighting with this power with the devilish beasticity threats to invade the small one continuously, clearing the room in which they built their lives carefully and consumed their residents (Sari & Wirasila, 2019;Suseni, 2020).…”
Section: Introductionmentioning
confidence: 99%